Preparation and Characterization of DHAD/HRP Co-loaded Multivesicular Liposomes (Journal of Fiber Bioengineering and Informatics, 2013)
The structure of carriers play an important role in the space distribution of different drugs, thereforethis paper studies multivesicular liposomes (MVLs), which have a unique nano-in-micro structure aspossible carriers in combination therapy. Horseradish peroxidase (HRP) and mitoxantrone hydrochloride(DHAD) were selected as model drugs for protein and small molecule drug respectively. The results showthat the MVLs are spherical and that the internal space is divided up into numerous compartments.The particle size ranged from 15 to 20 μm and the system was stable according to the zeta potentials. Invitro release studies display that the DHAD/HRP co-loaded MVLs has better sustained release profilesthan one drug alone, and the MVLs exhibited an orderly release behavior which suggested that MVLsmight be used as drug carriers in combination therapy applications.